2010
DOI: 10.1002/ajmg.b.31066
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic covariance between autistic traits and intelligence: Findings from a longitudinal twin study

Abstract: Intellectual disability is common in individuals with autism spectrum conditions. However, the strength of the association between both conditions and its relevance to finding the underlying (genetic) causes of autism is unclear. This study aimed to investigate the longitudinal association between autistic traits and intelligence in a general population twin sample and to examine the etiology of this association. Parental ratings of autistic traits and performance on intelligence tests were collected in a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
(58 reference statements)
0
28
1
Order By: Relevance
“…Average range is defined as two standard deviations either side of the mean, so this would mean an IQ of over 70. Further, it has been shown that IQ and autistic traits show limited genetic covariance [55]. It is therefore reasonable to infer that IQ differences are unlikely to confound the conclusions drawn from the current study.…”
Section: Discussionmentioning
confidence: 69%
“…Average range is defined as two standard deviations either side of the mean, so this would mean an IQ of over 70. Further, it has been shown that IQ and autistic traits show limited genetic covariance [55]. It is therefore reasonable to infer that IQ differences are unlikely to confound the conclusions drawn from the current study.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study has found a modest negative correlation between autistic traits and IQ (r= -.27), which was mainly explained by communication problems (Hoekstra, Happé, Baron-Cohen & Ronald, 2010). However, the authors stress that autistic traits and IQ are mostly independent.…”
Section: Limitationsmentioning
confidence: 77%
“…Since the study was conducted online, we were unable to assess IQ. Previous studies have found that there is a negative correlation between autistic traits and IQ (r= -.27) (Hoekstra, Happé, Baron-Cohen & Ronald, 2010).…”
Section: Limitationsmentioning
confidence: 91%